Air Bersih, Hidup Sehat : Edukasi Sanitasi Untuk Masyarakat Sehat di Kelurahan Selumit Pantai Kota Tarakan - Muntiari, Novita Ranti; Fathul Khair Tabri; Syamsiah; Muhammad Aris; Muliady; Asma; Lily Herawati (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
Access to safe water and adequate sanitation is a crucial factor in maintaining public health, particularly in coastal areas with high population density such as Selumit Pantai Subdistrict, Tarakan City. Various challenges, including environmental conditions, limited supporting infrastructure, and suboptimal sanitation practices among the community, have the potential to increase the risk of environment-related diseases. In response to these conditions, this Community Service activity was conducted as an educational effort through the provision of information and assistance related to clean water and sanitation. The activity involved resource persons from the Tarakan City Water Supply Company (PDAM) and Health Promotion lecturers, who delivered materials on water quality and utilization, clean and healthy living behaviors, and the prevention of environmental-based diseases. The implementation employed an interactive approach through lectures, discussions, and question-and-answer sessions to ensure the material was easily understood by the community. The objective of this activity was to improve community knowledge, awareness, and attitudes regarding the importance of proper clean water management and sanitation, thereby encouraging the sustainable adoption of healthy behaviors. Through synergy between practitioners and academics, this activity is expected to support improvements in the health status of coastal communities and contribute to health development in Tarakan City